The Development of Open and Distance Learning Model based on the Common ASEAN Tourism Curriculum: Unit D2.TTG.CL3.11 “Lead Tour Group in a Responsible Manner” - Tuti Elfrida; Handayani Rahayuningsih; Rina Widiastuti; Carlos Iban; Marc Alfer Sevilla; Suwanne Thammaratthara; Prattana Sutthisak (SEAMEO SEAMOLEC, 2023)
Each country in the ASEAN region agreed to cooperate in various fields, including the economy, which was later called the ASEAN Economic Community (AEC). This step also leads to the disclosure of human resources and labor. For the sake of uniformity, it is necessary to standardize the competencies that apply in ASEAN, so that the mobilization of professional personnel can be realized properly. In the field of tourism, one of the efforts to support the AEC is the Common ASEAN Tourism Curriculum (CATC). In its implementation, CATC has not made much use of the development of technology, information, and communication, so it is necessary to develop learning strategies in the field of technology-based tourism, especially those that can be accessed more broadly and more easily. This research then aims to develop a open and distance learning (ODL) strategy in the tourism sector, as well as to formulate an open and distance learning model for vocational higher education in the tourism sector that is in accordance with the characteristics of the region. This research focuses on the tour operation division which is more specific in travel service, namely the competency unit “Lead Tour Group in a Responsible Manner”. The development of this model includes several ouputs, such as e-module, podcast, demonstration video, as well as PPT and Voice over. Research data collection techniques were carried out through quantitative methods by having questionnaire, involving students who are participants of the ODL trial. The application of ODL for this is deemed to have been in accordance with the interests and needs of the participants' studies, but some learning media seems necessary to be added so that they can be accepted more clearly and increase participants' understanding of the presented material.